The Role of Experiential Avoidance and Parental Control in the Association Between Parent and Child Anxiety - Emerson, Lisa-Marie; Ogielda, Claire; Rowse, Georgina (Frontiers in Psychology, 2019)
Parenting behavior and practices contribute to the intergenerational relationship between parent and child anxiety, with parental control being a consistent predictor of child anxiety. Parental experiential avoidance refers to how a parent copes with their internal world in the context of parenting. Little is known about how this relatively new parenting concept relates to child anxiety. The current study tested the indirect effect of parent anxiety on child anxiety through parental control and parental experiential avoidance; the indirect effect of parent anxiety on parental control through parental experiential avoidance; and the moderating effect of parental experiential avoidance on the relationship between parental control and child anxiety. Using a cross-sectional design, parents (N = 85) from a community sample of 8-12-year-old children self-reported on a survey measuring parent anxiety, child anxiety, parental control, and parental experiential avoidance. A hierarchical regression indicated that parental experiential avoidance significantly predicted child anxiety and accounted for further variance in child anxiety, over and above parental control. There was an indirect effect of parent anxiety on child anxiety through parental control and parental experiential avoidance. Parental experiential avoidance moderated the relationship between parental control and child anxiety, such that the relationship was only significant at high levels of parental experiential avoidance. The current study provides support for the role of parental experiential avoidance in an intergenerational understanding of anxiety. Future research should replicate the study with a clinical sample. Theoretical and practice implications are considered.